The palatability and tolerability of deferasirox taken with different beverages or foods. Issue 9 (23rd April 2013) - Goldberg, Stuart L.; Giardina, Patricia J.; Chirnomas, Deborah; Esposito, Jason; Paley, Carole; Vichinsky, Elliott
Abstract Background Deferasirox is a once‐daily, oral iron chelator that was developed out of a need for a long‐acting, conveniently‐administered chelator for patients with transfusional hemosiderosis. The approved mode of administration requires taking deferasirox on an empty stomach with water, apple juice, or orange juice to limit variation in bioavailability. This required administration schedule might not be palatable for patients. Additionally, approximately one‐quarter of patients experience mild to moderate gastrointestinal (GI) symptoms, which may pose additional challenges, particularly in the younger and older age ranges. We present a trial to assess the palatability and safety of various administration modes of deferasirox in pediatric and adult patients. Procedures Participants rated palatability in a 4‐week run‐in phase, where deferasirox was administered per label. Subsequently, patients rated several administration modes during a 3‐month assessment phase. Results Palatability was more favorable during the assessment phase, with 47% of patient ratings for palatability being favorable while only 38% were favorable during the run‐in phase. The most highly rated choice was deferasirox taken with a soft food at breakfast. In addition, there was an indication of improved GI tolerability during the assessment phase (symptoms were reported in 37% of patients during run‐in and 32% during the assessment phase; rates of diarrhea decreased significantly). Although trough PK values increased, no major new toxicities were observed. Conclusions These data indicate that different administration options may improve palatability and GI tolerability, which could have a positive impact on treatment adherence. (ClinicalTrials.gov number, NCT00845871) Pediatr Blood Cancer 2013;60:1507–1512. © 2013 Wiley Periodicals, Inc.